Efektivitas Rod Visual Management System (RVMS) Terhadap Motivasi Kerja Karyawan PT Shimano Batam - Narti Eka Putria (Universitas Putera Batam, 2014)
The purpose of this study is to also learn how where efktivitas system used in the company, from this study are expected to provide benefits for the company in Batam, especially PT Shimano Batam, regarding the effectiveness of information systems RVMS PT Shimano Batam For Employees in doing their job. This study attempts to examine how the Effectiveness of Information Systems Employee Motivation RVMS influence on Shimano PT Batam. This study uses one independent variable and one dependent variable. The impact of the independent variables was analyzed by simple regression model. The results showed that there is a relationship of mutual dependence between variables significantly related.